Psychopathology of the Situation in Gestalt Therapy: A Field-Oriented Approach (2023) Edited by Margherita Spagnuolo Lobb and Pietro Andrea Cavaleri. Routledge. ISBN: 9781032322025 - Greer White (Psychotherapy and Counselling Journal of Australia)
Reviewed by the founder and former co-director of Gestalt Therapy Brisbane, _Psychopathology of the Situation in Gestalt Therapy: A Field-Oriented Approach_ (2023) addresses the suffering experienced by people in a post-pandemic world. Representing the work of the Italian Gestalt Institute, this book is applicable to all psychotherapists. It is written in two parts. The first part advances an exciting, relational gestalt therapy theory that can inform modern practice. The second part offers in 11 chapters case studies and theoretical discussions to working with clients in difficult clinical situations. Moving beyond the intra-psychic to a holistic, embodied perspective, this collection of works by experienced practitioners and researchers blends practical applications with theories encompassing neuroscience, identity, diversity, reciprocity, aesthetics, anthropology, phenomenology, and sociology.